Disease or Release? A Content Analysis on How is Menopause Framed in Romanian Online Media - Voicu, Ilona (Technium Social Sciences Journal, 2020)
Menopause is a natural biological event in every middle-aged woman life, but despite this universal character, the main ways to perceive this phenomenon are, often, “constructed” by social instances such as medicine or popular culture. The paper presents the main results of a traditional quantitative content analysis conducted on the six most popular Romanian online magazines for women (Avantaje.ro, Femeia.ro, Unica.ro, Elle.ro, Cosmopolitan.ro, Libertatea pentru femei.ro), and on three most visited websites with medical content (reginamaria.ro, medlife.ro, and csid.ro), in order to establish which are the main approaches regarding menopause. The content analysis was focused on the gender of the author and/or source of information, on types of words that are used in association with menopause, and photographs in articles. The results depict a predominant negative image of menopause, as a phase in women’s life marked by health issues. Also, an important difference from other analyzes of how menopause is presented in the media is that the implications of menopause on the sex lives of menopausal women are no longer taboo. Additionally, the infertility, as expression of loosing reproductive abilities, especially when we talk about premature menopause, seems to be another big associated issue, according to the research data. Using these results as starting point of discussion, the main topics that framed menopause in ROU online media are placed in the wider context: its role as social instance that could influence women’s perceptions about their menopausal experiences, considered socially relevant only if they are “useful bodies”, with intact reproductive capacities.